ANALYSIS OF THE IMPACT OF INVESTMENT, REGIONAL SPENDING, AND UNEMPLOYMENT RATE ON ECONOMIC GROWTH IN DKI JAKARTA PROVINCE, 2014-2023 - Andhika Rizaldi; Dita Dismalasari Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the effects of investment, regional government expenditure, and the unemployment rate on economic growth in DKI Jakarta Province during the 2014–2023 period. Economic growth is proxied by Gross Regional Domestic Product (GRDP) at current prices, while the independent variables include Domestic Investment (PMDN), Regional Revenue and Expenditure Budget (APBD), and the open unemployment rate. The analysis applies multiple linear regression using Stata, supported by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results confirm that the data meet all classical assumptions, indicating that the regression model is reliable and appropriate. Simultaneously, the three independent variables significantly influence GRDP, as indicated by a Prob > F value of 0.0024 and an adjusted R-squared of 0.8426, meaning that 84.26% of GRDP variation is explained by the model. However, partial testing reveals that only PMDN has a positive and statistically significant effect on economic growth, while APBD and the open unemployment rate show no significant impact. These findings suggest that strengthening domestic investment plays a crucial role in driving economic growth in DKI Jakarta, while improving the effectiveness of regional spending and unemployment policies remains necessary.